'Guns for Hire': Morality, Law & Ethics - MacAndrew, Ben (2013)
Since the dawn of civilisation, the provision of military services for profit has been a dominant factor in shaping the world as recognised today. Although shunned by the international community at large and vilified as ‘dogs of war’, the end of the Cold War and the prevalence of Capitalism has presented an opportunity for ‘mercenaries’ to seek legitimacy through the corporatisation of their activities; with both the onset of globalisation and increasingly restricted military budgets resulting in a renewed demand for their services.